Mentoring women in STEM: empowering through social technologies for enhanced inclusivity and professional growth. A case study - Pacheco Figueroa, Coral J.; Alvarez Lemus, Mayra A. (Frontiers in Education, 2025)
The use of social technologies for on-line training of women in STEM (Science Technology Engineering and Mathematics) areas was explored for empowering women. Here, a case study on the implementation of a mentoring program focused on fostering the professional careers of women from the Juarez Autonomous University of Tabasco (UJAT), at the southeast of Mexico is presented. By means of an international initiative from the British Council, 32 participants were trained as mentors and mentees at UJAT, and further matched to accomplish a 3 months mentoring relationship. Throughout the sessions, the participants’ advances in soft skills (assertiveness, networking, leadership, active listening, self-confidence, ability to set SMART objectives, among others) were analyzed, showing how the use of social technologies promoted the professional development of women through empowerment as a strategy for reducing the gender gap in scientific and technological careers in Latin America.